Imagining a digital history of women writers - Sanz, Amelia (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In this paper we present some important contributions that digital technologies are supplying to the research in the field of women writers history, mainly in Europe. We use arguments to assess these contributions in three domains: massive digitization processes in libraries and archives concerning women writers; collections, repositories and data-base ; digital tools for analysis. We claim for feminist perspectives, critical ones, in any digital development.
Keywords: digitalization; digital collections; digital tools; women writers